2018
DOI: 10.1039/c8qi00533h
|View full text |Cite
|
Sign up to set email alerts
|

Chiral molecular fluoridosilicates and their twin polymerization for the preparation of fluorine-doped mesoporous silica and microporous carbon

Abstract: The synthesis of organic–inorganic hybrid materials, microporous carbon and fluorine-doped mesoporous silica by the twin polymerization of pentacoordinated fluoridosilicates is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…This will have direct influence on material properties including hydrophobicity, refractive index and elastic modulus. [108] In summary, the fluoride-initiated TP of spirocyclic silicon compounds 1 and 22 behaves differently as compared to common acid-and base-catalyzed TP (see earlier). [108] It should be noted that the added fluoride assists as a reactant rather than as a catalyst.…”
Section: Figurementioning
confidence: 87%
See 4 more Smart Citations
“…This will have direct influence on material properties including hydrophobicity, refractive index and elastic modulus. [108] In summary, the fluoride-initiated TP of spirocyclic silicon compounds 1 and 22 behaves differently as compared to common acid-and base-catalyzed TP (see earlier). [108] It should be noted that the added fluoride assists as a reactant rather than as a catalyst.…”
Section: Figurementioning
confidence: 87%
“…Consecutive calcination of the respective hybrid materials gave fluorine-doped silica with surface areas of up to 239 m 2 g À 1 . [108] Furthermore, within the studies it could be shown that also hybrid materials were accessible by applying the additive assisted TP of twin monomer 1 with [Bu 4 N]F or KF producing microporous carbon with a BET surface area of 1219 m 2 g À 1 and mesoporous silica with a surface area of 687 m 2 g À 1 . Oxidation of the potassium-Scheme 12.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations